Length-weight models and condition factors of fishes from Okpara Stream, Oueme River, Northern-Benin - SIDI IMOROU, Rachad; ADITE, ALPHONSE; SOSSOUKPE, EDMOND; ABOU, YOUSSOUF (My University, 2019)
Length frequency distributions, length-weight models and condition factors of 21 dominant fish species of the Okpara stream (Oueme River) were examined in Northern-Benin in order to evaluate the well-being of these fish taxa. Samplings were made monthly from December 2015 to May 2017 with seines, gill nets hawks and a total of 9,302 individuals werecollected. Fish abundance ranged from 53 individuals for Mormyrus rume to 2,818 for Hemichromis fasciatus. Standard length (SL) varied from 1.2 cm (Coptodon guineensis) to 51.8 cm (Chrysichthys nigrodigitatus). Length-weight regressions equations showed significant (p < 0.05) correlation coefficients (r) ranging between 0.4664 and 0.9949 with slopes (b) between 2.2262 and 3.7703 corresponding to isometric, positive allometric and negative allometric growths displayed by 4, 8 and 9 species, respectively. Condition factors K varied between 0.17 - 29.38 and species with higher well-being were Oreochromis niloticus with K=29.38, Hyperopisius bebe (K = 20.14), Coptodon zillii (K = 19.25), Mormyrus rume (K = 17.13) and Sarotherodon galilaeus multifasciatus (K = 16.16). A sustainable exploitation of these fishes requires an ecosystem restoration scheme including habitat protection, species conservation and an ecological follow-up of the Okpara stream.
Keywords: Allometry; condition factor; ecosystem restoration; NorthernBenin; Oueme River.